Integrating primary care providers through the seasons of survivorship - Chaput, G. (Curr Oncol, 2019)
Traditionally, the role of primary care providers (pcps) across the cancer care trajectory has focused on prevention and early detection. In combination with screening initiatives, new and evolving treatment approaches have contributed to significant improvements in survival in a number of cancer types. For Canadian cancer survivors, the 5-year survival rate is now better than it was a decade ago, and the survivor population is expected to reach 2 million by 2031. Notwithstanding those improvements, many cancer survivors experience late and long-term effects, and comorbid conditions have been noted to be increasing in prevalence for this vulnerable population. In view of those observations, and considering the anticipated shortage of oncology providers, increasing reliance is being placed on the primary care workforce for the provision of survivorship care. Despite the willingness of pcps to engage in that role, further substantial efforts to elucidate the landscape of high-quality, sustainable, and comprehensive survivorship care delivery within primary care are required. The present article offers an overview of the integration of pcp ■ Survivorship care coordination; ■ Knowledge of survivorship; ■ pcp-led clinical environments; ■ Models of survivorship care; ■ Health policy and organizational advocacy.